Communicating Difference through Social Media: The Case of a Kenyan Facebook Group. Issue 4 (1st October 2016) - Gachau, James
ABSTRACT: Following Butsch's (2007) observation that 'the sheer scale of modern media corporations overwhelms the relatively minute institutions of the public sphere, as a skyscraper enshadows a small public park', the argument made here is that modern democratic societies are subjugated by a public sphere overwhelmed by the interests of the dominant social classes. Social media are stepping into the void thus created by the corporatised and institutionalised media. The article interrogates the ways in which a Facebook group, founded upon the principle of counterpublics à la Nancy Fraser (1990), communicates difference against the overwhelmingly and oppressively Christian Kenyan public sphere. The research found that the social media group provides its members with a community where they can form identities and voices not predicated upon the claims and assumptions of the dominant public. The group, in opposition to religion, dogma and tradition, identifies with freethinking and atheism, and challenges the suppositions of Christian dogma and perceived bigotry.